COMMUNITY PERSPECTIVE ON THE ACTIVITIES OF THE SHOLAWAT ASSEMBLY DURING THE PANDEMIC - Nanda Tri Ifkinil Wulandari; Agus Machfud Fauzi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
During the pandemic it is not prohibited by the government and WHO. The public can still carry out activities procedurally. However, religious activities still hold. However, in the religious community they carry out in accordance with government recommendations. One of the activities that do not escape the characteristics of Muslims is the prayer assembly. The sholawat assembly is an activity carried out by a group of people who have such great love for the Prophet and God. The purpose of this study was to look at the views of the Anggaswangi village community, especially Youth Mosques on sholawat assembly activities during the pandemic. The method used is a qualitative research method, because researchers need to make an in-depth approach with the Anggaswangi village community in order to obtain data directly from informants. The theory used is the theory of social behavior from Max Weber. The theory explains that according to Weber, human individuals in society are creative actors and social reality is not a static tool of coercion of social facts. That is, human actions are not determined by norms, habits, values, and so on which are included in the concept of social facts. The initial assumption of this research is that the people of Anggaswangi village view religious activities as a form of love for God, but activities such as Majeliis Sholawat can also be used as activities to pray to God due to the situation during the Covid-19 pandemic. The theory used is the theory of social behavior from Max Weber. The theory explains that according to Weber, human individuals in society are creative actors and social reality is not a static tool of coercion of social facts. That is, human actions are not determined by norms, habits, values, and so on which are included in the concept of social facts. The initial assumption of this research is that the people of Anggaswangi village view religious activities as a form of love for God, but activities such as Majeliis Sholawat can also be used as activities to pray to God due to the situation during the Covid-19 pandemic. The theory used is the theory of social behavior from Max Weber. The theory explains that according to Weber, human individuals in society are creative actors and social reality is not a static tool of coercion of social facts. That is, human actions are not determined by norms, habits, values, and so on which are included in the concept of social facts. The initial assumption of this research is that the people of Anggaswangi village view religious activities as a form of love for God, but activities such as Majeliis Sholawat can also be used as activities to pray to God due to the situation during the Covid-19 pandemic. Human individuals in society are creative actors and social reality is not a static tool of the coercion of social facts. That is, human actions are not determined by norms, habits, values, and so on which are included in the concept of social facts. The initial assumption of this research is that the people of Anggaswangi village view religious activities as a form of love for God, but activities such as Majeliis Sholawat can also be used as activities to pray to God due to the situation during the Covid-19 pandemic. Human individuals in society are creative actors and social reality is not a static tool of the coercion of social facts. That is, human actions are not determined by norms, habits, values, and so on which are included in the concept of social facts. The initial assumption of this research is that the people of Anggaswangi village view religious activities as a form of love for God, but activities such as Majeliis Sholawat can also be used as activities to pray to God due to the situation during the Covid-19 pandemic.